Synergy between Village Heads and Youth Organizations in Implementing Village Development in Botumoito District - Miranda Nihe; Roni Lukum; Nopiana Mozin (SEAN Institute, 2026)
Village development is an important part of national development that emphasizes community participation and collaboration between local institutions. In this context, participatory village development requires synergy between the village government and community elements, including Karang Taruna as a youth organization that has a strategic role in supporting the implementation of development programs. However, in practice, the involvement of Karang Taruna in several villages is not fully optimal, thus affecting the effectiveness of village development. This study aims to analyze the challenges of cooperation between village heads and Karang Taruna, identify the cooperation models applied, and explain the development of synergy between the two in the implementation of village development with collaborative, participatory governance to realize sustainable development and community empowerment, especially the younger generation in the Botumito sub-district. This study uses a descriptive approach using qualitative research types that only describe the meaning of data or phenomena that can be captured by the researcher, by showing the evidence. This study uses data collection techniques in the form of interviews, observation, and documentation. In-depth interviews were conducted with competent sources in their fields, including village heads, BPD, Karang Taruna, and community leaders. To validate the research data, triangulation techniques were used, with qualitative data analysis. The results showed that the main challenges to collaboration lie in communication, the division of roles and authority, and resource support. Two models of collaboration were identified: a more effective and participatory partnership (coordination) model in Potanga and Tapadaa Villages, and a top-down instructive (hierarchical) model in Tutulo and Hutamonu Villages. The development of synergy indicates that villages with open communication and a clear division of roles have more inclusive, participatory, and sustainable development.